NEED OF ESTIMATION OF LEARNING IN MOOC COURSES USING LEARNING ANALYTICS: A GAP IDENTIFICATION - Kapil Mohan Garg,Dr Adarsh Garg (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Introduction: Learning analytics(LA) is an evolving field which utilises analytic tools like BI, social media data analytics, etc., to improve learning and education. It is basically the measurement, collection, analysis and reporting of data about learners and their contexts, for purposes of understanding and optimizing learning and the environments in which it occurs. This process generates lots of data that need to analyzed and put to fruitful use so that learning can be enhanced. Based on literature review, this paper presents the need for learning estimation on MOOC Courses using LA. Methodology: A four stage process is followed to formulate this study as a literature review and gap identifications that concerns Learning Analytics in MOOC. The stages includes extensive search of related literature from reputed national and international academic works, studying the literature and selecting the principal studies, examining and tabulation of various expects of studies, like objectives, analysis tools used, major findings, etc. and reporting the review in form of gap analysis. Findings and discussion: Findings suggests that apart from LA approaches, its implementation in education and learning is more predominant objective. Sophisticated predictive and regression models are applied on gathered data for obtaining better meaningful insights. But no significant study focuses on Management education or Indian Context or both. Findings shows that all online courses are doing traditional evaluation using online assignments, tests etc. to issue certificates. It is found that there are still numerous unexplored areas related to LA and MOOC method to estimate/calculate/ proposes the quantification of learning of students/learners in MOOC courses. Conclusion and recommendations: In relation to LA and MOOC, it is opined that there is very crucial insight on estimation of learning is required in MOOC for quantification of learning of students/learners for the development of powerful and beneficial learning services.